2021
DOI: 10.1109/tnsre.2021.3088637
|View full text |Cite
|
Sign up to set email alerts
|

Phase/Amplitude Synchronization of Brain Signals During Motor Imagery BCI Tasks

Abstract: In the last decade, functional connectivity (FC) has been increasingly adopted based on its ability to capture statistical dependencies between multivariate brain signals. However, the role of FC in the context of brain-computer interface applications is still poorly understood. To address this gap in knowledge, we considered a group of 20 healthy subjects during an EEG-based hand motor imagery (MI) task. We studied two well-established FC estimators, i.e. spectral-and imaginarycoherence, and we investigated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…From the function activity aspect, the work on synchronization between the signal amplitudes and the phase has been discussed (Rosenblum et al, 1996 ; Nolte et al, 2004 ). It hypothesizes that integrating these complementary features will allow a better characterization of the BCI-related mental states and that including them in the feature extraction block, which is helpful to increase the BCI accuracy compared to standard approaches solely based on power spectra (Cattai et al, 2019 ). In this way, the phase relationship between EEG signals on the prefrontal and parietal lobes will be characterized by PLV.…”
Section: Discussionmentioning
confidence: 99%
“…From the function activity aspect, the work on synchronization between the signal amplitudes and the phase has been discussed (Rosenblum et al, 1996 ; Nolte et al, 2004 ). It hypothesizes that integrating these complementary features will allow a better characterization of the BCI-related mental states and that including them in the feature extraction block, which is helpful to increase the BCI accuracy compared to standard approaches solely based on power spectra (Cattai et al, 2019 ). In this way, the phase relationship between EEG signals on the prefrontal and parietal lobes will be characterized by PLV.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, subjects sat quietly 50 cm away from a screen, and the stimulus material (500 mL full drinks) was placed in the right-hand position, facing the table [ 14 ]. The subjects were asked to imagine repeatedly moving his/her right hand (i.e., grasping and lifting) in the state of open eyes.…”
Section: Methodsmentioning
confidence: 99%
“…Giacomo [ 13 ] found significant changes in alpha and beta power in the frontal lobe region when subjects performed hand motion imagination tasks. Cattai [ 14 ] also selected the hand imagination task and found that network features based on spectral coherence increased in the sensorimotor region during motor imagery. Although these studies suggest that activation of different brain regions is associated with changes in motor-imagery-related rhythm characteristics, the exact relationship between the two remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, subjects were not asked to perform MI techniques. Recent evidence suggests that it may be possible to use indices of functional connectivity using MI tasks ( Cattai et al, 2021 ). More studies are needed to understand the differences observed.…”
Section: Methodsmentioning
confidence: 99%